2017
DOI: 10.3892/or.2017.5733
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Mycobacterium tuberculosis infection promotes lung tumor growth through enhancing Treg development

Abstract: Abstract. Lung cancer is the most common malignancy in humans. An increased population of CD4 + Foxp3 + regulatory T cells (Tregs) in the tumor-associated microenvironment plays an important role in cancer immune evasion. The exact role and the involved mechanisms of concomitant H37Rv infection in non-small cell lung cancer (NSCLC) development are still not clear. Here, we showed that H37Rv infection promoted NSCLC cell growth with a higher percentage of Tregs found in draining lymph nodes. We also determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
7
0
2
Order By: Relevance
“… 16 Zhou et al demonstrated that mycobacterium tuberculosis infection could induce increased expression of PD-L1 in macrophage by Akt-mTORC1 pathway. 17 Recently, Inman et al found that 11 of 12 patients with BCa who failed BCG immunotherapy exhibited extremely intense PD-L1 expression within the BCG granulomas of tumor tissue. 18 Heo et al also showed that normal epithelial tissues regenerated after surgical resection and BCG immunotherapy, had low expression of PD-L1, while recurred tumor showed high expression of PD-L1 after surgical resection and BCG immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 16 Zhou et al demonstrated that mycobacterium tuberculosis infection could induce increased expression of PD-L1 in macrophage by Akt-mTORC1 pathway. 17 Recently, Inman et al found that 11 of 12 patients with BCa who failed BCG immunotherapy exhibited extremely intense PD-L1 expression within the BCG granulomas of tumor tissue. 18 Heo et al also showed that normal epithelial tissues regenerated after surgical resection and BCG immunotherapy, had low expression of PD-L1, while recurred tumor showed high expression of PD-L1 after surgical resection and BCG immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Nuestros hallazgos con respecto a las co-morbilidades son coherentes con lo reportado en la literatura científica, donde la principal causa de muerte en pacientes con TBC es la co-infección con SIDA y las complicaciones derivadas como otras infecciones oportunistas 1,21,22 . Se encontró en este estudio concomitancia entre TBC y cáncer en 16% de los pacientes; este hallazgo cada vez es más frecuente en la literatura médica, especialmente en cáncer de pulmón, lo que demuestra la necesidad de tamizar la infección latente por TBC de los pacientes con cáncer y evaluar la presencia de malignidad en pacientes con diagnóstico de TBC en zonas endémicas 19,23 .…”
Section: Resultsunclassified
“…La edad es variable en diferentes estudios realizados en instituciones de alta complejidad 16,17 . Con respecto al tipo de TBC extrapulmonar, la meningoencefalitis tuberculosa fue la más frecuente, la que se ha asociado a mayor mortalidad 18,19 .…”
Section: Discussionunclassified
“…Besides, the upregulation of PD-L1 expression and induction of lung carcinoma by IFN-γ have been revealed [ 30 ]. Similarly, in vitro and in vivo concomitant H37Rv infection in non-small cell lung cancer showed that lung cancer progression facilitated by enhancing Treg cells proportion and the upregulation of PD-L1 expression that induced by H37Rv as a part of M.tb lineage 4 [ 31 ]. In the current study, based on the expression of IFN-γ in response to the infection with M.tb L4.5 sub-lineage, compared to L3-CAS1 sub-lineage, this expression profile might be favor for better control of M.tb L4.5 sub-lineage strain compared to L3-CAS1 sub-lineage in infected host cell, in addition may contribute to the pathogenesis and deterioration of lung cancer during infection with M.tb L4.5 sub-lineage strain.…”
Section: Discussionmentioning
confidence: 99%